GROWING THE SPIRIT OF PATRIOTISM THROUGH CULTURAL ACTIVITIES - Nuning Nurma Dewi; Niswatin Niswatin (Ecopreneur.12, 2023)
One of the efforts to defend the Unitary State of the Republic of Indonesia is to instill patriotism in the younger generation. This effort can be done through educational institutions so that it can be measured. The unstoppable influence of foreign culture can be anticipated by introducing local culture. This study aims to reveal regional culture as a medium to foster a spirit of patriotism in the younger generation. The urgency and contribution of this research is to promote the spirit of patriotism through cultural activities. This qualitative research uses data collection techniques through observation, interviews, and documentation. The data analysis technique uses interactive data analysis by Miles and Huberman. The results showed that through cultural activities in the form of Kupang dance and a folk song entitled re kayo rek, they were able to foster an attitude of patriotism, namely being proud as a citizen of Sidoarjo, knowing the meaning and meaning of the Kupang dance, knowing the importance of the song re kayo rek.Â